Rearrange the equation by subtracting what is to the right of the equal sign from both sides of the equation : 

                     9*2+6*y-(6)=0 

Step by step solution :
Step  1  :Pulling out like terms :

 1.1     Pull out like factors :

   12 + 6y  =   6 • (y + 2) 

Equation at the end of step  1  :Step  2  :Equations which are never true :

 2.1      Solve :    6   =  0

This equation has no solution.
A a non-zero constant never equals zero.

Solving a Single Variable Equation :

 2.2      Solve  :    y+2 = 0 

 Subtract  2  from both sides of the equation : 
 
                     y = -2 

One solution was found :                   y = -2


Processing ends successfully